Who Controls the Internet? - Lemos, Joelma Galvão de; Menezes Coelho, Daniel (Revista de Psicologia, 2022)
Through this theoretical study, it is possible to verify that the Internet, initially created as a network that would allow the access and decentralization of the circulation of information, the viability of communication and, consequently, the access of all to information platforms, businesses, services and online social networks, it is not a random network, and its operating properties force us to reassess the general idea, according to which the network would be a space for freedom of expression, justice, democracy and social transformation. Currently, it is the large digital technology companies that have mastered the architecture of the network and dictated the way it should work, thus occupying an economic and political role in our society. This is because the vast majority of public and private services, as well as the lives of each one, have been crossed by the digital, which caused changes in social organizations, and consequently in the modes of contemporary subjectivation.